Serpula and Spiraserpula (Polychaeta, Serpulidae) from the Tropical Western Atlantic and Gulf of Guinea - Rolando Bastida-Zavala (ZooKeys, 2012)
Six species of Serpula and Spiraserpula were identified, mainly, from the material of the expeditions of the Rosenstiel School of Marine and Atmospheric Science, University of Miami, including two new species of Serpula. Serpula madrigalae sp. n. from the Turks and Caicos has a tube with five longitudinal ridges, four rows of alveoli and a medium-sized shallow symmetrical opercular funnel with 17 radii, and an inner surface with opercular tubercles. Serpula vossae sp. n. from the Western Caribbean and Bahamas has a tube with 6–8 longitudinal ridges, and a large, deep symmetrical opercular funnel, with 21–33 radii, and a smooth inner surface. Serpula cf. vermicularis, recorded from the Gulf of Guinea (tropical eastern Atlantic), is distinguished from the nominal species in possessing fewer opercular radii (33–39) and the lack of a proximal rasp in the bayonet chaetae; tubes are missing. The distribution range is extended for the three known Spiraserpula species found in the collections, S. caribensis, S. karpatensis and S. ypsilon.